Pelagic Ecosystem Characteristics Across the Atlantic Water Boundary Current From Rijpfjorden, Svalbard, to the Arctic Ocean During Summer (2010–2014) - Hop, Haakon; Assmy, Philipp; Wold, Anette; Sundfjord, Arild; Daase, Malin; Duarte, Pedro; Kwasniewski, Slawomir; Gluchowska, Marta; Wiktor, Józef M.; Tatarek, Agnieszka; Wiktor, Józef; Kristiansen, Svein; et al. (Frontiers in Marine Science, 2019)
The northern coast of Svalbard contains high-arctic fjords, such as Rijpfjorden (80oN 22o30’E) that face the Arctic Ocean. This area has experienced higher sea and air temperatures and less sea ice in recent years, and ecosystem models predict increasing temperatures in this region. Part of the West Spitsbergen Current (WSC), which transports relatively warm Atlantic water and heat along the continental slope west of Svalbard, bypasses these fjords on its route in the Arctic Ocean. In this setting, it is of interest to study the present structure of water masses and plankton in the Atlantic Water (AW) boundary current. This study describes oceanographic, chemical and plankton conditions during summer (July-August, 2010-2014) from Rijpfjorden across the shelf and continental slope to the Arctic Ocean. Atlantic water resided over the upper continental slope and also protruded onto the shelf area, occasionally during summer and autumn. The interplay between the intrusion of AW and meltwater affects the chemical balance of the region by making carbonate chemistry and nutrient concentrations highly variable depending on season, depth and distance along the gradient. However, glacier and land drainage did not seem to constitute a significant nutrient source in this region. All years were characterized by a late summer post-bloom situation with low surface nutrient concentrations and subsurface chlorophyll a maxima. Chlorophyll a maxima coincided with the bottom of the euphotic zone and the nutricline illustrating that phytoplankton optimized growth at the opposing gradients of light and nutrients. In terms of biomass, the protist community was dominated by nanoplankton (2-20 m), in particular unidentified flagellates and their protozoan grazers, dinoflagellates and ciliates. Prymnesiophytes often prevailed at subsurface depths associated with the chlorophyll a maximum and diatoms contributed a large share of protist biomass at stations closer to the ice edge. The boreal Calanus finmarchicus and Oithona similis dominated AW over the slope and on the outer part of the shelf, whereas Calanus glacialis and neritic zooplankton (Pseudocalanus, Parasagitta elegans and meroplankton) dominated the cold water masses inside Rijpfjorden. Continued climate warming is expected to increase the contribution of boreal species and pelagic production during summer and autumn.